Cerebro-Placental Ratio in Women with Hypertensive Disorders of Pregnancy: A Reliable Predictor of Neonatal Outcome - Vikram Patil; Sahana Gowda; Sudha Das; KB Suma; Rudresh Hiremath; Sachin Shetty; Vinay Raj; MR Shashikumar (Journal of Clinical and Diagnostic Research, 2019)
Introduction: About 10 million women develop pre-eclampsia per year. Intra-Uterine Growth Restriction (IUGR) is a common complication of Hypertensive disorders of pregnancy, due to failure of normal placental invasion and development. Identification of the pregnancies at risk for preventable perinatal morbidity and mortality is a primary goal of obstetric care. Doppler flow studies are an important adjunct to fetal biometry in identifying the fetus at risk of adverse outcome. Cerebro-Placental Ratio (CPR) incorporates data of both Umbilical artery and Middle cerebral artery and is a better index than using either of them alone for predicting adverse perinatal outcome. Aim: To determine the role of CPR in women with Hypertensive disorders of pregnancy, so as to assess the fetus at greater risk of adverse perinatal outcome. Materials and Methods: This cohort study was done in JSS Hospital, Mysore on subjects satisfying inclusion and exclusion criteria. The study period was from November 2016 to November 2018. A total of 128 antenatal women of >32 weeks of gestation were selected for the study; preliminary data were recorded and subjected to ultrasound scan. Association between CPR and other categorical variables were analysed using chi-square test. Pearson’s Correlation coefficient was used to show correlation between CPR and other quantitative variables. Results: Among pregnancy-related hypertension, preeclampsia was the most common cause (71.1%), followed by eclampsia (20.3%). The five minute APGAR score was ≤7 in 21.8% while the rest had a score of >7 (78.2%). There was significant association between CPR and the Ultrasonographic gestational age, birth weight and fetal outcome. Lower APGAR score at 5th minute was associated with abnormal CPR values, especially the babies with APGAR score of ≤7 at 5 minutes. Conclusion: Abnormal CPR is valuable in predicting the outcome of hypertensive disorders in pregnancy. Perinatal outcomes namely, preterm delivery, caesarean section and fetal compromise like low birth weight, lower APGAR at 5 minutes, requirement of NICU care can be predicted with lower CPR.